Innovations in minimally invasive techniques in animal surgery (International Seven Journal of Multidisciplinary, 2024)
Objective: To analyze the main innovations in minimally invasive techniques in animal surgeries. In the field of Veterinary Medicine, CMI is becoming increasingly popular, being seen as an alternative to traditional surgical techniques. Procedures such as laparoscopy, endoscopy, laser therapy, and 3D robotics are revolutionizing the field, bringing benefits such as less pain, lower risk of infections, and faster recovery of patients. Given the growth in demand from animal caregivers and the advancement of technology, it is expected that these techniques will continue to improve and become more accessible. Laparoscopy allows for less invasive diagnoses in internal cavities, while endoscopy allows abdominal surgeries with smaller incisions. The healing of injuries and wounds is accelerated by laser therapy, which facilitates pain relief and functional recovery. At the same time, 3D robotics offers precision in the production of customized prostheses and surgical guides, contributing to better surgical outcomes. Final thoughts: Despite initial barriers such as high costs and the learning curve, CMI is constantly expanding, improving standards of veterinary care. With the advancement of technologies and the increased demand for less invasive techniques, these innovations are expected to continue to grow and become more accessible, raising the quality of animal care